(untitled) (KULT_online, 2013)
It’s hard to imagine the study of culture anymore without the concept of hybridity. The monograph Unrein und vermischt. Postkoloniale Grenzgänge durch die Kulturgeschichte der Hybridität und der kolonialen »Rassenbastarde« (Impure and Mixed: Postcolonial Border Crossings through the Cultural History of Hybridity and Postcolonial "Racial Bastards"), published in 2010 by Kien Nghi Ha, describes the long career of this concept in the European and German history of ideas. The author, who is a scholar within the fields of cultural studies and political sciences, makes a convincing case for a renewed politicization und contextualization of this trendy term. In a collection of essays from 2012 edited by Ha, Asiatische Deutsche. Vietnamesische Diaspora and Beyond (Asian Germans: Vietnamese Diaspora and Beyond), this call is put into practice within the context of the Vietnamese-Asian diaspora in Germany in the most productive and impressive fashion, particularly against the background of racist stereotyping and empowering self-definitions.